2022
DOI: 10.21873/invivo.12834
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Duration of Axillary Lymph Node Swelling After COVID-19 Vaccination: Japanese Case Report and Literature Review

Abstract: Background/Aim: COVID-19 vaccination is now performed in most of the world to limit the spread of the disease. The first mRNA vaccine was approved in clinical settings and has specific side effects including axillary lymph node swelling, which can be misdiagnosed as breast cancer metastasis. The timing of axillary lymph node swelling and its duration are unclear. Here, we present a Japanese case and review of the existing literature. Case Report: We report the case of a 67-year-old woman with breast calcificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…According to a retrospective review of 951 patients who underwent 18 Several studies reported on the expected time course for resolution of lymphadenopathy. 10,13,24,25 In the largest study on axillary lymphadenopathy following COVID-19 vaccination with long-term follow-up of 6 months, the time to resolution of reactive lymphadenopathy was variable, with persistent lymphadenopathy observed up to 43 weeks following vaccination. Lymphadenopathy was found as early as 1 day after the first dose of vaccine and as late as 71 days after the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…According to a retrospective review of 951 patients who underwent 18 Several studies reported on the expected time course for resolution of lymphadenopathy. 10,13,24,25 In the largest study on axillary lymphadenopathy following COVID-19 vaccination with long-term follow-up of 6 months, the time to resolution of reactive lymphadenopathy was variable, with persistent lymphadenopathy observed up to 43 weeks following vaccination. Lymphadenopathy was found as early as 1 day after the first dose of vaccine and as late as 71 days after the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…A case study involved a 64-year-old woman with breast calcification who was assessed for breast cancer via ultrasonography six months before her first SARS-CoV-2 vaccine, and again 7 days after the vaccine due to obvious lymph node enlargement in the vaccinated arm. Six months later, a follow-up examination revealed that the lymph node was still swollen, although somewhat reduced, even though there was no evidence of breast cancer [92].…”
Section: Potential For Damage To the Thymic Epithelium And Accelerate...mentioning
confidence: 98%
“…The exact mechanism of how the COVID-19 vaccine may cause lymphadenopathy and increased WBC uptake is unclear, although it is postulated that the increased immune response following vaccination causes an immune mediated inflammatory response in the area surrounding the vaccination site, and immune cells in the nearby nodes may proliferate as they become exposed to the vaccine. This type of reactive lymphadenopathy has been seen in multiple other vaccines in the past including measles, anthrax, H1N1, bacille Calmette-Guérin, and human papillomavirus vaccines 11,12 . Post-COVID reactive axillary lymphadenopathy has been reported to persist longer than 6 months and up to 43 weeks after vaccination 11,12 .…”
mentioning
confidence: 94%
“…This type of reactive lymphadenopathy has been seen in multiple other vaccines in the past including measles, anthrax, H1N1, bacille Calmette-Guérin, and human papillomavirus vaccines. 11 , 12 Post-COVID reactive axillary lymphadenopathy has been reported to persist longer than 6 months and up to 43 weeks after vaccination. 11 , 12 The Moderna mRNA vaccine was also significantly more associated with lymphadenopathy compared with Pfizer.…”
mentioning
confidence: 99%
See 1 more Smart Citation